Post-mortem interval estimation of human skeletal remains by micro-computed tomography, mid-infrared microscopic imaging and energy dispersive X-ray mapping. Issue 7 (7th April 2015) - Longato, S.; Wöss, C.; Hatzer-Grubwieser, P.; Bauer, C.; Parson, W.; Unterberger, S. H.; Kuhn, V.; Pemberger, N.; Pallua, Anton K.; Recheis, W.; Lackner, R.; Stalder, R.; et al.
<x xml:space="preserve">Abstract</x> In this study different state-of-the-art visualization methods were evaluated to study human skeletal remains for the determination of the post-mortem interval (PMI).